Brain power - borrowing from biology makes for low power computing [bionic ear]. - Sarpeshkar, R. (IEEE spectrum)
This paper describes the recent advances in the field of neuromorphic engineering, more generally, biologically inspired electronics. This paper focuses on the work being done to develop bionic ears. A key area of interest is understanding the scheme that allows low-power analog processing in the ear followed by digitization. Researchers at MIT have developed a bionic ear processor that does the job of the digital signal processor, is small enough to be implanted, and could run on a 2 gram battery needing a wireless recharge only every two weeks. This effort has also led to the design of a new algorithm that can improve the performance of ordinary cochlear implants and other speech processors. The team is currently working on designing an ultrawideband spectrum analyzer that can simultaneously tune into radio signals all the way from the FM radio bands to Wi-Fi bands.